2019
DOI: 10.1016/j.bpsc.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Social and Environmental Factors as Modulators of Brain Dysfunction: Time to Focus on Developing Non-Western Societies

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…All these programmes were developed alongside research centres or universities, and they had not yet been scaled‐up to the national level. However, more recently, new services have been implemented in the region, new evidence has been produced and a collaborative network for the study of psychosis has been created to move the field forward in the region (N. A. Crossley et al, 2019; N. Crossley et al, 2019). Hence, we aimed to review the state of implementation of EIP services in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…All these programmes were developed alongside research centres or universities, and they had not yet been scaled‐up to the national level. However, more recently, new services have been implemented in the region, new evidence has been produced and a collaborative network for the study of psychosis has been created to move the field forward in the region (N. A. Crossley et al, 2019; N. Crossley et al, 2019). Hence, we aimed to review the state of implementation of EIP services in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric analyses of the human hippocampus and hippocampal formation were initially performed retrospectively, and some of these studies identified volume reductions in adolescent, adult and ageing individuals who had experienced early-life adversity [161][162][163] . However, retrospective studies in specific populations are susceptible to confounding 100,164 , and later studies failed to replicate these findings 165,166 . More recently, prospective approaches have aimed to clarify the relationship between early-life adversity and imaging measures of brain circuit development 110,167 .…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Nowadays, the environment is in the spotlight of not only companies but also academic researches (Argacha et al, 2018;Barr-Anderson et al, 2018;Crossley et al, 2018). Therefore, both academics and companies search for useful methods for considering environmental aspects.…”
Section: Introductionmentioning
confidence: 99%